2016
DOI: 10.4082/kjfm.2016.37.4.221
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Vitamin D and Health-Related Quality of Life in Korean Adults

Abstract: BackgroundWe examined the relationship between vitamin D status and health-related quality of life, and explored other related factors in the general Korean population.MethodsWe used data from the 2007–2012 Korea National Health and Nutrition Examination Survey on 14,104 adults, aged 20–49 years, who had consented to serum vitamin D measurement and answered health-related quality of life questions. EuroQol-5 was used for measurement. Serum vitamin D levels were measured at intervals of 0–9.99, 10–19.99, 20–29.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…Так, данные Фрамингемского исследования показали увеличение риска развития СД2 на 40% у лиц с минимальным уровнем 25(ОН)D в сыворотке крови через 7 лет от начала наблюдения [17]. Аналогичные данные были получены и в перекрестном исследовании, проведенном среди жителей Южной Кореи в возрасте старше 20 лет, где СД2 чаще встречался у лиц с недостатком и дефицитом витамина D по сравнению с лицами, чей уровень 25(OH)D в сыворотке крови был выше 75 нмоль/л [18]. Похожие результаты были продемонстрированы и в исследовании с участием более пяти тысяч жителей Австралии, по данным которого, риск развития СД2 также оказался выше у лиц с низким уровнем 25(OH)D, а увеличение концентрации 25(OH)D на каждые 25 нмоль/л ассоциировалось со снижением риска СД на 24% [19].…”
Section: дефицит витамина D и риск развития сахарного диабета 2 типаunclassified
“…Так, данные Фрамингемского исследования показали увеличение риска развития СД2 на 40% у лиц с минимальным уровнем 25(ОН)D в сыворотке крови через 7 лет от начала наблюдения [17]. Аналогичные данные были получены и в перекрестном исследовании, проведенном среди жителей Южной Кореи в возрасте старше 20 лет, где СД2 чаще встречался у лиц с недостатком и дефицитом витамина D по сравнению с лицами, чей уровень 25(OH)D в сыворотке крови был выше 75 нмоль/л [18]. Похожие результаты были продемонстрированы и в исследовании с участием более пяти тысяч жителей Австралии, по данным которого, риск развития СД2 также оказался выше у лиц с низким уровнем 25(OH)D, а увеличение концентрации 25(OH)D на каждые 25 нмоль/л ассоциировалось со снижением риска СД на 24% [19].…”
Section: дефицит витамина D и риск развития сахарного диабета 2 типаunclassified
“…Without considering these confounders, misleading results can be obtained. In the study by Kim et al, 4) a univariate analysis revealed a correlation between a low vitamin D level and a low quality of life score; however, its significance was lost when age, sex, income, education level, and disease state were considered.…”
mentioning
confidence: 95%
“…In the present issue, Kim et al examined the relationship between vitamin D status and health-related quality of life using KNHANES. 4) In interpreting vitamin D-related study results, correlation should not be understood as causation. Diets composed of vitamin D–rich foods such as dairy products and salmon also contain high levels of other healthy nutrients.…”
mentioning
confidence: 99%
“…D vitamini düzeyini değerlendirmek için en güvenilir yol dolaşımda en fazla bulunan 25(OH)D düzeyinin saptanmasıdır (1,8). Son yapılan çalışmalarda, bazı hastalıklarda ve toplum bazlı çalışmalarda D vitamini ile yaşam kalitesi arasında ilişki araştırılmıştır (7,(9)(10)(11)(12). AA ve vitiligolu hastalarda yaşam kalitesinin azalmasına katkıda bulunan faktörleri inceleyen birçok araştırma yapılmıştır fakat bu hastalarda yaşam kalitesi ile D vitamini arasındaki ilişki araştırılmamıştır.…”
unclassified
“…/mL arasında ise D vitamini yetersizliği ve 30 ng/mL ve üstünde ise normal değer olarak kabul edildi(7,12). D vitamini düzeyi çalışma grubumuzun %29'unda 10 ng/mL'nin altında, sadece %12'sinde 30 ng/mL'nin üzerinde bulundu.…”
unclassified